Embodied pedagogy and ecological ethics: Internalising environmental values through the Pakarena Anida dance in South Sulawesi - Pramana, Andi Dwi Resqi; Astuti, Tri Marhaeni Pudji; Malarsih, Malarsih; Sinaga, Syahrul Syah (Journal of Environment and Sustainability Education, 2025)
Global ecological crises demand sustainability education that integrates cultural and ecological values beyond formal and Western-oriented frameworks. Traditional performing arts offer holistic pedagogical resources through embodied, symbolic, and participatory practices, yet their potential remains underexplored in sustainability discourses. In Indonesia, the Pakarena Anida Dance of South Sulawesi exemplifies how ritual gestures, ornate costumes, and narrative symbolism function as cultural texts transmitting ecological ethics and community values. However, limited scholarship has examined how female dancers operate as custodians of both cultural heritage and environmental responsibility. This study employs a descriptive qualitative design, drawing on anthropology, semiotics, and cultural studies to analyse the symbolic representation of female dancers in South Sulawesi traditional performances. Multi-sited fieldwork was conducted in Makassar City, Wajo Regency, and Toraja Regency, involving 29 purposively selected informants—including cultural leaders, senior dancers, troupe members, and audiences. Data were collected through performance observation, semi-structured interviews, and documentation of manuscripts and visual records. Analysis followed Miles and Huberman’s interactive model, supported by thematic and interpretive strategies. Findings reveal three key insights. First, Pakarena Anida embodies conservation values through symbolic movements—such as bowing and circular formations—that signify humility and ecological balance. Second, the dance functions as informal education, with rehearsals and performances serving as “schools without walls” where intergenerational ecological and moral wisdom is transmitted. Third, costumes, music, and ritualised gestures operate as cultural codes that internalise local values, reinforcing identity, humility, and responsibility across generations.